Tunnel Fire Testing and Modeling The Morgex North Tunnel Experiment - Borghetti, Fabio; Derudi, Marco; Gandini, Paolo; Frassoldati, Alessio; Tavelli, Silvia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book aims to cast light on all aspects of tunnel fires, based on experimental activities and theoretical and computational fluid dynamics (CFD) analyses. In particular, the authors describe a transient full-scale fire test (~15 MW), explaining how they designed and performed the experimental activity inside the Morgex North tunnel in Italy. The entire organization of the experiment is described, from preliminary evaluations to the solutions found for management of operational difficulties and safety issues. This fire test allowed the collection of different measurements (temperature, air velocity, smoke composition, pollutant species) useful for validating and improving CFD codes and for testing the real behavior of the tunnel and its safety systems during a diesel oil fire with a significant heat release rate. Finally, the fire dynamics are compared with empirical correlations, CFD simulations, and literature measurements obtained in other similar tunnel fire tests. This book will be of interest to all engineers and public officials who are concerned with the nature, prevention, and management of tunnel fires.
Safety in road tunnels -- The research project and partners involved -- The fire tests in the Morgex North tunnel -- The test results -- Evaluation of the consequences on the users safety -- Conclusions.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Security systems; Computer simulation; Civil engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Security Science and Technology; Computer Modelling; Civil Engineering